2020
DOI: 10.1111/cxo.12960
|View full text |Cite
|
Sign up to set email alerts
|

Higher order aberrations, refractive error development and myopia control: a review

Abstract: Evidence from animal and human studies suggests that ocular growth is influenced by visual experience. Reduced retinal image quality and imposed optical defocus result in predictable changes in axial eye growth. Higher order aberrations are optical imperfections of the eye that alter retinal image quality despite optimal correction of spherical defocus and astigmatism. Since higher order aberrations reduce retinal image quality and produce variations in optical vergence across the entrance pupil of the eye, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 193 publications
(446 reference statements)
1
54
0
Order By: Relevance
“…Soft contact lenses with different refractive profiles may contribute to reduce myopia progression by 30%-50%. 5 However, positive dysphotopsia is often reported by Table 3. Lower-order, higher-order and total aberrations for a pupil diameter of 3 mm and 5 mm in each contact lens patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soft contact lenses with different refractive profiles may contribute to reduce myopia progression by 30%-50%. 5 However, positive dysphotopsia is often reported by Table 3. Lower-order, higher-order and total aberrations for a pupil diameter of 3 mm and 5 mm in each contact lens patients.…”
Section: Discussionmentioning
confidence: 99%
“…4 It has been reported that a reduction in myopia progression might be achieved by using a centre-distance, dual-focus (DF) contact lens design through the reduction of off-axis hyperopia. [4][5][6] These new designs are being used clinically for myopia control. 2,3 Even though visual acuity (VA) remains acceptable in the majority of patients, many still complain about insufficient quality of vision and dysphotopsia.…”
Section: Introductionmentioning
confidence: 99%
“…Dual-focus designed lenses also produced positive SA in 3 mm pupil size, but conversely, in greater pupil sizes of 4 mm, a higher negative value of 4th order SA was found, and even more so in the 5 mm pupil size. These ndings show that the changes in HOA induced by dual-focus designs (such as MiSight) are substantially more pupil-dependent than the center-distance MFCL designs 31,34 and shows the role of SA whose magnitude differently affects the myopia control. 34 Previous MASS studies have also reported an increase on monocular light disturbance perception 28 and near-vision worsening 26 in subjects wearing MiSight (study group) compared with subjects wearing single-vision spectacles (control group).…”
Section: Discussionmentioning
confidence: 80%
“…These ndings show that the changes in HOA induced by dual-focus designs (such as MiSight) are substantially more pupil-dependent than the center-distance MFCL designs 31,34 and shows the role of SA whose magnitude differently affects the myopia control. 34 Previous MASS studies have also reported an increase on monocular light disturbance perception 28 and near-vision worsening 26 in subjects wearing MiSight (study group) compared with subjects wearing single-vision spectacles (control group). Nevertheless, over 2 years of follow-up there could be seen a signi cant binocular attenuation effect, and a consequent decrease in the monocular light disturbance.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation